THE USE OF ANIMATED SHORT FILM AS MEDIA FOR TEACHING ENGLISH NARRATIVE WRITING - Merindriasari, Kiki; Supardi, Iwan; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract : This research aims to find out the effectiveness of the animated short film as media for teaching English narrative writing on the third grade students of SMA Negeri 8 Pontianak in academic year 2014/2015. The research method that used is a quasi-experimental and the research design that used is non-equivalent control group design. The study sample is 60 students. The result of data analysis showed that mean score of the experimental class was higher (from 36.67 to 75.33) than control class (from 41.33 to 62.50). The computation of the effect size with the score 1.48 ( > 1.00) shows that the use of animated short film as media has the strong effect for teaching English narrative writing. Â Keywords : writing, narrative text, animated short film. Â Abstrak : Penelitian ini bertujuan untuk menemukan keefektifan dari film pendek animasi sebagai media untuk mengajar menulis narrative dalam bahasa inggris pada siswa kelas tiga dari SMA Negeri 8 Pontianak tahun ajaran 2014/2015. Metode penelitian yang digunakan adalah eksperimen semu dengan rancangan penelitian yang digunakan adalah non-equivalent control group. Sampel penelitian ini adala 60 siswa. Hasil analisis data menunjukan bahwa nilai rata-rata dari kelas eksperimen lebih tinggi (36,67-75,33) daripada kelas kontrol (41,33-62,50). Perhitungan dari ukuran efek dengan nilai 1,48 (>1,00) menunjukan bahwa kegunaan dari film pendek animasi sebagai media memiliki efek yang kuat untuk mengajar menulis narative dalam bahasa inggris. Â Kata Kunci : menulis, teks narative, film pendek animasi